PROGRAM LIFELONG LEARNING MERDEKA BELAJAR EDUKASI KOGNITIF MEWUJUDKAN SDGS GOAL 4 GUNA MENINGKATKAN KUALITAS SDM DI SLB MEDAN - Oktaviandi Bertua Pardede; Ranto Luspen Manalu; Diwehati Salawajo; Sapriliyani Gulo; Nur Indah Sidebang; Tabas Gabe Mulia Siagian (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
Lifelong Learning can be experienced by every learning community. Instilling the values of academic education with the aim of improving the quality of Human Resources can trigger schools to seek to optimize innovative learning. Freedom to learn cognitive education as a reference for lifelong learning programs seeks to realize inclusive and equitable quality education. It is believed that the Sustainable Development Goals (SDGs) that spur Indonesia's human development index need to be carried out at the Markus Medan Special School. This program is conducted for Markus SLB students for 1.5 months. The method used is participatory and experimental. During its implementation, students participate in building learning activities, so that data analysis is carried out qualitatively and quantitatively. The collected data is processed interactively and continuously until the data is saturated. The data are also interpreted descriptively through quantitative data measures. The results show that Markus Special School students can participate in cognitive education learning. Continuously, student learning products always influence their learning motivation, especially the results of drawing and motor skills of students. The experimental results showed a significant difference before and after experiencing cognitive education learning activities. As many as 60% of students get test scores above average.